Relationships among Subjective Cognitive Impairment, Oral Function, and Social Capital in Community-dwelling Older Adults - Ekuni, Daisuke; Washio, Norifumi; Morita, Manabu; Takeuchi, Noriko; Sawada, Nanami; Sawada, Koichi (Ronen Shika Igaku, 2022)
Purpose：The number of older adults with dementia is increasing rapidly in Japan. However, an effective treatment for dementia has not yet been established. The purpose of this study was to investigate the relationships among oral function, social capital, and cognitive decline in community-dwelling older adults.　Methods：Cognitive function was assessed using the items of the Kihon Check List. Binomial logistic regression analysis was performed with the presence of cognitive function as the dependent variable. A covariance structure equation was developed to examine the effect of each factor on the impairment in subjective cognitive function.　Results：Seventy-three subjects（24 males and 49 females, mean age 80.0±10.6 years）were analyzed. The results of binomial logistic regression analysis showed that depression（odds ratio（OR）6.392, 95% confidence interval（CI）1.208-33.821）, oral diadochokinesis（ODK）/ta/（OR 0.633, 95% CI 0.457-0.962）, and rural social capital（OR 0.927, 95% CI 0.859-0.999）were significantly associated with subjective cognitive impairment. The relationships among the factors obtained by the covariance structural equation showed that older age, a lower frequency of ODK /ta/, and a more depressive status tended to be related to worse subjective cognitive function. A higher frequency of ODK /ta/, less depressive status, and a higher rural SC value tended to be associated with less subjective cognitive impairment.　Conclusions：This study suggested that depression, tongue dexterity and rural social capital were associated with subjective cognitive impairment in a study of older adults in rural areas.